PENGARUH PENAMBAHAN LIMBAH KULIT PINUS TERHADAP HASIL PIROLISIS LIMBAH PLASTIK HDPE SEBAGAI BAHAN BAKAR ALTERNATIF - Sigit Mujiarto; Rany Puspita Dewi; Ali Suhadla (Politeknik Negeri Cilacap, 2024)
Waste often becomes a problem for society. Pyrolysis is considered an effective solution to reduce waste and can produce end products that can be utilized as energy sources. This study uses HDPE plastic waste with variations in the addition of pine bark waste at 0%, 25%, 50%, and 75%, with a total mass of 500 grams and the addition of 100 grams of bentonite catalyst. The pyrolysis process is carried out for 120 minutes at a temperature of 320Â°C. The aim is to examine the effect of adding pine bark on the pyrolysis oil yield of HDPE plastic as an alternative fuel using parameters of fuel physical characteristics, including density, viscosity, and calorific value. The best results show that the variations of adding 50% and 75% pine bark waste have physical characteristics equivalent to B20 and B30 fuels, with density, viscosity, and calorific values of 0.8307 g/ml, 2.341 cSt, and 10,644.894 cal/g for the 50% pine bark variation, and 0.8367 g/ml, 2.467 cSt, and 10,491.863 cal/g for the 75% pine bark variation, respectively.